If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -4) = 11 Reorder the terms: x(-4 + 2x) = 11 (-4 * x + 2x * x) = 11 (-4x + 2x2) = 11 Solving -4x + 2x2 = 11 Solving for variable 'x'. Reorder the terms: -11 + -4x + 2x2 = 11 + -11 Combine like terms: 11 + -11 = 0 -11 + -4x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -5.5 + -2x + x2 = 0 Move the constant term to the right: Add '5.5' to each side of the equation. -5.5 + -2x + 5.5 + x2 = 0 + 5.5 Reorder the terms: -5.5 + 5.5 + -2x + x2 = 0 + 5.5 Combine like terms: -5.5 + 5.5 = 0.0 0.0 + -2x + x2 = 0 + 5.5 -2x + x2 = 0 + 5.5 Combine like terms: 0 + 5.5 = 5.5 -2x + x2 = 5.5 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x2 = 5.5 + 1 Reorder the terms: 1 + -2x + x2 = 5.5 + 1 Combine like terms: 5.5 + 1 = 6.5 1 + -2x + x2 = 6.5 Factor a perfect square on the left side: (x + -1)(x + -1) = 6.5 Calculate the square root of the right side: 2.549509757 Break this problem into two subproblems by setting (x + -1) equal to 2.549509757 and -2.549509757.Subproblem 1
x + -1 = 2.549509757 Simplifying x + -1 = 2.549509757 Reorder the terms: -1 + x = 2.549509757 Solving -1 + x = 2.549509757 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 2.549509757 + 1 Combine like terms: -1 + 1 = 0 0 + x = 2.549509757 + 1 x = 2.549509757 + 1 Combine like terms: 2.549509757 + 1 = 3.549509757 x = 3.549509757 Simplifying x = 3.549509757Subproblem 2
x + -1 = -2.549509757 Simplifying x + -1 = -2.549509757 Reorder the terms: -1 + x = -2.549509757 Solving -1 + x = -2.549509757 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -2.549509757 + 1 Combine like terms: -1 + 1 = 0 0 + x = -2.549509757 + 1 x = -2.549509757 + 1 Combine like terms: -2.549509757 + 1 = -1.549509757 x = -1.549509757 Simplifying x = -1.549509757Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.549509757, -1.549509757}
| 3+12+5x-7-3x= | | 2/5*3/8 | | 1/5(20x-5)=4(x+1) | | x^2-19x=28 | | 0.11-0.01(x+1)=0.02(4-x) | | 5y-13=52 | | 21*2= | | 9X+4/22=4 | | 10-(9-x)=3+2x | | 1/6*1 | | (x/(x-2))=(2/(x-2))-(2/3) | | 4x+-7=6 | | (4*32)-(19/3) | | 5(x-1)+1=2x+3(-2+x) | | 1/2x+2-1/4x=3 | | 1/6*-2 | | -2(17x-4)+7(5x-7)-8=8-7 | | 7*2-n= | | 2y/3=7 | | (-3/4)/(2/3+5/6) | | -5(3a-a)=-3(2-a) | | 4(4x-4)-3(5x-2)=-10 | | 6x+3n-2x-n= | | 7x=ab | | s+5/2s+10=38 | | 4x-38384894934=5 | | 5x+6(-2x-5)=-38-9x | | x^2+0.5x=0 | | -3(4.7y-5.8)+15.1y=9.5 | | -6/8/9/6 | | 4(2n-1)=(3n+5)+7 | | 1.6(z+7)-(5.9+0.6z)=-7+6 |